Global Claims in Construction - Haidar, Ali.; SpringerLink (Online service). (London Springer London, 2011)
Recent years, a number of global claims have failed because they were presented without any systematic analysis, justification or proper calculation of losses. Hence, Global Claims in Construction highlights these issues as well as the importance of understanding causation, factual necessity and the courts? attitude and approach to global claims. Global Claims in Construction addresses the principles of global claims and their calculation methodologies in detail through extensive references to literature, case law and a real world case study. It aims to be a valuable resource for professionals working in the construction industry, as well as students in construction and engineering.
1. Introduction -- 2. Contract Law - Principles and Doctrines -- 3. Construction Contracts - Obligations, Vitiations and Remedies -- 4. Delays and Disruptions Provisions -- 5. Damages and Calculation of Losses -- 6. Global Claims - An Overview -- 7. Global Claims - Total Cost Methodology and Substantiation -- 8. Global Claim _ A Case Study.
Electronic reproduction.
Keywords: Construction contracts; Breach of contract; Property (International law).; Electronic book